Evaluation of treatment on unilateral cleft lip and palate complete dextra to the quality of life: 4-year follow-up: Case report - Alda Arifialda; Helmi Siti Aminah; Lisda Damayanti (Indonesia Prosthodontic Association, 2023)
Treatment for the patient with cleft lip and palate (CLP) requires an interdisciplinary team concerned with improving the patient’s quality of life. This case evaluates the influence of comprehensive therapy on unilateral CLP complete dextra within a 4-year follow-up. A 4-days-old female patient visited a government hospital in Bandung after being referred to a pediatric clinic in the same hospital. The patient was born at 3.2 kg weight with no underlying medical conditions or syndromes. Intraoral examination revealed cleft soft and hard palate and separated alveolar segment. Extraoral examination revealed cleft lip unilateral dextra and shortened columella. The patient underwent compre-hensive therapy including presurgical NAM (PNAM), labioplasty, nasoalveolar molding (NAM), veloplasty, speech therapy, and palatoplasty. It is concluded that early treatment of PNAM reduces the severity of the orofacial deformi-ty, induced the reposition of soft & hard tissue and there’s an improvement in intelligibility and production of pharyng-eal sounds and velopharyngeal closure when using intravelar veloplasty in palatal repair along with NAM. In the fourth year of life, the patient has capable on communicates with intelligibility pronounce with relative adequate arch.